(untitled) (Global Journal of Science Frontier Research, 2023)
According to the theory of noncommutative quantum gravity 1 2 we calculate the self-interaction of gravitons in momentum space It shows that the self-interaction of gravitons makes the gravitational field deviate from the inverse square law By calculating the metric it can be ob- tained that the stronger the gravitational source the stronger the energy- momentum of the excited gravitons and the stronger the gravitational effect produced by the self-interaction of gravitons Maybe be it can be used to explain dark matter and the Pioneer anomaly